Partisipasi Petani Kopi dalam Pengembangan Agrowisata Kiadan di Subak Abian Sari Boga Kecamatan Petang Kabupaten Badung - DIANTARI, I GUSTI AYU PUTU; PARINING, NYOMAN; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
Participation of Coffee Farmers in Developing Agrotourism in Kiadan Village, Petang District, Badung Regency.  Subak Abian Sari Boga develops agro-tourism because most of the villagers are coffee farmers. The journey of Kiadan Agrotourism has been quite long and there have been many problems in its development. So it is necessary to analyze the level of participation of coffee farmers in developing Kiadan Agrotourism. The purpose of this research is to analyze the level of participation of coffee farmers in developing Kiadan Agrotourism in Subak Abian Sari Boga, Petang District, Badung Regency. This research was conducted at Kiadan Agrotourism, selected by purposive sampling or deliberately, carried out since April 2021. The sample in this study was determined by the random sampling method, where the total sample was 40 coffee farmers. The data analysis method used in this study uses a descriptive qualitative method. Based on the results of the research and discussion that has been presented, it can be concluded that the level of participation of coffee farmers in developing Kiadan Agrotourism is in the very high category because the conditions of coffee farmers are very supportive for participation. The participation of coffee farmers is at the level of Citizen Power.